Association between tobacco consumption and periodontal diseases among type 2 diabetes mellitus patients - Shaikh Zakir Mahmud; Mohammad Shoheilul Amin (Wolters Kluwer Medknow Publications, 2016)
Background: Tobacco use may be an independent, modifiable risk factor for impaired glucose tolerance, and noninsulin-dependent diabetes mellitus. The use of both combustible and noncombustible forms of tobacco increases the risk of coronal and root caries, periodontal diseases, and oral cancer. Aims: This cross-sectional study was conducted to find out the relationship between tobacco consumption and occurrence of periodontal diseases among type 2 diabetes mellitus patients. Subjects and Methods: A total 120 type 2 diabetic patients attended at a diabetic center for routine check-up over a period of 6 months fulfiled the eligibility criteria were selected consecutively. To get the target sample quickly non-randomized purposive sampling technique was followed using a pre-tested semi-structured questionnaires and a checklist. The severity of periodontal diseases was followed according to American Academy of Periodontology (1999). The data were analyzed using the software SPSS, Version 11.5 (SPSS Inc., Chicago, IL, USA). software. Associations were assessed using the Chi-square test and logistic regression analysis. Results: Among the participants 22.5% were current smoker and 31.7% always chewed betel leaf. Education level indicated strong association with chewing betel leaf on unadjusted (odds ratio = 0.56 [0.39-0.82]) (P < 0.003). Chewing betel leaf (Paan) was significantly associated with the occurrence of periodontal diseases (P = 0.048). In addition, knowledge about cigarette smoking and chewing tobacco increases periodontal diseases indicated strong associations with current smoker as well as betel leaf chewer (P = 0.000). Conclusions: The relationship between smoking and chewing betel leaf and periodontal diseases provide strong evidence that tobacco products could be in a straight line responsible for developing periodontal diseases.